Uji Efektivitas Sterilisasi dan Desinfeksi Ventilator Mekanik Di RSUD Dr. Moewardi - Indraputri, Rizky Saraswati; Saptawati, Leli; Setijanto, Eko (Nexus Biomedika, 2014)
Background: Mechanical ventilator is a semicritical equipment that often contacts with mucous membrane or skin. The use of mechanical ventilator for long term can cause some complication, one of them is Ventilator-Associated Pneumonia (VAP) which is the common nosocomial infection in ICU. Sterilization and disinfection of mechanical ventilator decrease microorganism infection. Every hospital has their own sterilization and disinfection procedure of mechanical ventilator. This research aims to examine the effectiveness of sterilization and disinfection of mechanical ventilator at RSUD Dr. Moewardi. Method: This was an analytic observational study using cross sectional design. Samples were taken from swab and circuit rinse of mechanical ventilator tube after sterilization and disinfection with storage and without storage process. A total of 30 samples were sampled for each tube and circuit based on the rule of thumb with consecutive sampling technique. Data were analyzed descriptively and tested using Chi Square test. Result: There were 30 samples from circuit rinse which were negative from contamination. In tube swab, there were 8 samples positive from contamination. In 15 samples of tube swab without storage process, there were 2 positive samples and 13 negative samples from contamination. In 15 samples of tube swab with storage process, there were 6 positive samples and 9 negative samples from contamination. The microorganisms of contaminants were Bacillus sp, Staphylococcus aureus, and Staphylococcus epidermidis. The statistical analyses showed no significant relationship between both storage processes either sterilization or disinfection of mechanical ventilator and microorganism contamination (p = 0.226). Conclusion: Sterilization and disinfection of ventilator circuit at RSUD Dr. Moewardi are effective. While sterilization and disinfection of mechanical ventilator are not yet effective. There is not a significant relationship between storage and the effectiveness of either sterilization or disinfection of mechanical ventilator. Keywords: sterilization, disinfection, mechanical ventilator Â